2018
DOI: 10.1007/s40846-018-0450-6
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Exercise Guidance System Based on Smart Clothing

Abstract: In this study, we designed and developed an intelligent exercise guidance system based on smart clothing. The system comprised smart clothing for electrocardiogram (ECG) signal acquisition and heart rate (HR) monitoring, an exercise control application program, and a cloud server. Music beats were used to guide the exercise routine. The use of an empirical mode decomposition (EMD)-based ECG signal denoising algorithm and a quadratic polynomial regression model (QPRM) of HR and running cadence (running steps pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…As shown in Figure 3 , for data-level fusion with a lower fusion level, in order to retain more detailed information of the original data, there is often no data preprocessing link. In data processing, first go through fusion calculation and then extract features on the basis of the fusion result to obtain the final result [ 20 ].…”
Section: Data Mining Methods and Multisource Data Fusion Algorithm Ba...mentioning
confidence: 99%
“…As shown in Figure 3 , for data-level fusion with a lower fusion level, in order to retain more detailed information of the original data, there is often no data preprocessing link. In data processing, first go through fusion calculation and then extract features on the basis of the fusion result to obtain the final result [ 20 ].…”
Section: Data Mining Methods and Multisource Data Fusion Algorithm Ba...mentioning
confidence: 99%
“…Its overall implementation process is different from M-DDPG in that the level of meta value network is higher, and other operations such as initialization and update of network parameters are consistent. In H-DDPG algorithm, the minimum cost function corresponding to the meta value network can be expressed as Eq (9).…”
Section: Plos Onementioning
confidence: 99%
“…The system integrated social information and collaborative information to predict user preferences, and it was found that the intelligent music recommendation system had superior performance [8]. Lin et al (2019) designed and developed an intelligent motion guidance system based on music beat guidance, tested the effectiveness of the system by using quadratic polynomial regression model based on signal denoising algorithm, and found that the system had good effect in motion guidance [9]. Fakhrhosseini and Jeon (2019) proposed an emotional intelligence system based on music regulation and found that multimodal perception could be effectively applied to the overall evaluation of driver's emotional state.…”
Section: Introductionmentioning
confidence: 99%
“…The smart clothing in this study was a smart vest, which was developed previously and the research focused on the technology incorporated into the vest and the accuracy of the data transmitted [15,16,17]. This paper describes the use of a smart vest in an actual home setting.…”
Section: Introductionmentioning
confidence: 99%